EXPLORATION OF STUDENTS’ SOCIAL EXPERIENCE THROUGH A BACKPACKER-BASED EXPERIENTIAL LEARNING AT MADRASAH IBTIDAIYAH ALAM - Fitria Martanti; Maskur; Ma’as Shobirin; Muhammad Ahsanul Husna (Program Studi Manajemen Pendidikan Islam, 2026)
This research is motivated by the importance of developing students’ social experiences in primary education through a contextual, experience-based learning approach. Learning centered solely on classroom activities is considered insufficient to provide opportunities for students to develop real social skills. This study aims to examine the implementation of backpacker strategies to improve students’ social experience, and the implications and challenges of these strategies at Madrasah Ibtidaiyah Alam Alfa Kids. This study uses a qualitative approach. Data was collected through observations, interviews, and documentation involving teachers and students as research subjects. Data analysis is carried out through the stages of data reduction, data presentation, and conclusion drawing to gain a comprehensive understanding of the implementation of backpacker strategies in learning. The results showed that implementing backpacker strategies made a real contribution to increasing students’ social participation, social adaptability, and social concern. Through systematically designed educational travel activities, students gain an authentic and meaningful learning experience. However, the program’s implementation still faces several challenges, including limited availability of companion teachers, implementation time, and the scope of activities. The conclusion of this study emphasizes that the backpacker strategy is an effective experience-based learning approach in supporting the social development of students at the Madrasah Ibtidaiyah level. This approach offers a more contextual, humanistic, and relevant learning process that meets students’ developmental needs